Influence of Financial and Climate Factors on Agricultural Industry Development - LUKPANOVA, Zhanar; TOYZHIGITOVA, Zhanar; ALINA, Gulzhan; JUMABEKOVA, Almagul; ORAZGALIYEVA, Arailym (Journal of Environmental Management and Tourism, 2020)
The development of the agro-industrial complex in Kazakhstan is an urgent problem for agricultural producers and insurers, since agriculture is in the zone of constant natural and economic risks, where the main share of risks is associated with weather events affecting the production of agricultural crops. In order to reduce negative factors in agriculture, to ensure the protection of the property interests of farmers in crop production from the consequences of adverse natural phenomena, animal husbandry, measures are being taken by the state and business, however, there are still problems that agricultural producers face.